2018
DOI: 10.1101/362418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoupling the variances of heterosis and inbreeding effects is evidenced in yeast’s life-history and proteomic traits

Abstract: Heterosis (hybrid vigor) and inbreeding depression, commonly considered as corollary phenomena, could nevertheless be decoupled under certain assumptions according to theoretical population genetics works. In order to explore this issue on real data, we analyzed the components of genetic variation in a population derived from a half-diallel cross between strains from Saccharomyces cerevisiae and S. uvarum, two related yeast species involved in alcoholic fermentation. A large number of phenotypic traits, either… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…In brief, the most important findings were: homeostasis of the interspecific hybrids observed at the trait level (da Silva et al 2015) and the predominance of interspecific heterosis at the proteomic level (Blein-Nicolas et al (2015)). A closer analysis of genetic variance components confirmed that observable phenotypic traits tended to exhibit higher additive genetic variance and lower interaction variance than proteomic traits (Petrizzelli et al, 2019).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In brief, the most important findings were: homeostasis of the interspecific hybrids observed at the trait level (da Silva et al 2015) and the predominance of interspecific heterosis at the proteomic level (Blein-Nicolas et al (2015)). A closer analysis of genetic variance components confirmed that observable phenotypic traits tended to exhibit higher additive genetic variance and lower interaction variance than proteomic traits (Petrizzelli et al, 2019).…”
Section: Introductionmentioning
confidence: 75%
“…We considered the genetic value of protein abundances and fermentation/life-history traits, rather than their measured/computed value. In a previous study, Petrizzelli et al (2019) decomposed the phenotypic value of a trait at a given temperature, P T , into its genetic, G T , and residual, , contributions:…”
Section: Genetic Value Of Protein Abundances and Fermentation/life-mentioning
confidence: 99%